2010
DOI: 10.1158/0008-5472.can-10-1712
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Cell-Initiated Signaling Promotes the Survival and Self-Renewal of Cancer Stem Cells

Abstract: Recent studies have demonstrated that cancer stem cells play an important role in the pathobiology of head and neck squamous cell carcinomas (HNSCC). However, little is known about functional interactions between head and neck cancer stem-like cells (CSC) and surrounding stromal cells. Here, we used aldehyde dehydrogenase activity and CD44 expression to sort putative stem cells from primary human HNSCC. Implantation of 1,000 CSC (ALDHþCD44þLinÀ) led to tumors in 13 (out of 15) mice, whereas 10,000 noncancer st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
250
0
13

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 232 publications
(273 citation statements)
references
References 36 publications
5
250
0
13
Order By: Relevance
“…The concept that a physical niche protects tumor cells during drug treatment has also been suggested for the perivascular space within the tumors. Indeed, recent work has highlighted a tumor reinitiating cells along tumor vessels, suggesting that these locations have a predictive role in tumor sensitivity to treatment (43,44). Bissel group demonstrated that ECs and factors deposited within their surrounding basement membrane may be a prime player within the dormant niche and revealed that stable microvasculature constitutes a dormant niche, whereas sprouting neovasculature sparks micrometastatic outgrowth (45).…”
Section: Discussionmentioning
confidence: 99%
“…The concept that a physical niche protects tumor cells during drug treatment has also been suggested for the perivascular space within the tumors. Indeed, recent work has highlighted a tumor reinitiating cells along tumor vessels, suggesting that these locations have a predictive role in tumor sensitivity to treatment (43,44). Bissel group demonstrated that ECs and factors deposited within their surrounding basement membrane may be a prime player within the dormant niche and revealed that stable microvasculature constitutes a dormant niche, whereas sprouting neovasculature sparks micrometastatic outgrowth (45).…”
Section: Discussionmentioning
confidence: 99%
“…In head and neck tumors, the vast majority of the stem cells are found within a 100 microns radius of a blood vessel (Krishnamurthy et al, 2010). Using the SCID mouse model of human tumor angiogenesis (Nör et al, 2001), it was observed that specific ablation of tumor associated endothelial cells with an inducible Caspase-9 results in the decrease in the fraction of head and neck cancer stem cells (Krishnamurthy et al, 2010).…”
Section: Stem Cell Nichementioning
confidence: 99%
“…Using the SCID mouse model of human tumor angiogenesis (Nör et al, 2001), it was observed that specific ablation of tumor associated endothelial cells with an inducible Caspase-9 results in the decrease in the fraction of head and neck cancer stem cells (Krishnamurthy et al, 2010). It is becoming increasingly evident that the molecular crosstalk between HNSCC and endothelial cells is mutually relevant (Neiva et al, 2009;.…”
Section: Stem Cell Nichementioning
confidence: 99%
See 2 more Smart Citations